Defining the Role of Cellular Immune Signatures in Diagnostic Evaluation of Suspected Tuberculosis. (31st July 2021) - Halliday, Alice; Masonou, Tereza; Tolosa-Wright, Mica R; Guo, Yanping; Hoang, Long; Parker, Robert; Boakye, Aime; Takwoingi, Yemisi; Badhan, Amarjit; Jain, Pooja; Marwah, Ishita; Berrocal-Almanza, Luis C; et al.
Abstract: Background: Diagnosis of paucibacillary tuberculosis (TB) including extrapulmonary TB is a significant challenge, particularly in high-income, low-incidence settings. Measurement of Mycobacterium tuberculosis (Mtb)-specific cellular immune signatures by flow cytometry discriminates active TB from latent TB infection (LTBI) in case-control studies; however, their diagnostic accuracy and clinical utility in routine clinical practice is unknown. Methods: Using a nested case-control study design within a prospective multicenter cohort of patients presenting with suspected TB in England, we assessed diagnostic accuracy of signatures in 134 patients who tested interferon-gamma release assay (IGRA)-positive and had final diagnoses of TB or non-TB diseases with coincident LTBI. Cellular signatures were measured using flow cytometry. Results: All signatures performed less well than previously reported. Only signatures incorporating measurement of phenotypic markers on functional Mtb-specific CD4 T cells discriminated active TB from non-TB diseases with LTBI. The signatures measuring HLA-DR + IFNγ + CD4 T cells and CD45RA − CCR7 − CD127 − IFNγ − IL-2 − TNFα + CD4 T cells performed best with 95% positive predictive value (95% confidence interval, 90–97) in the clinically challenging subpopulation of IGRA-positive but acid-fast bacillus (AFB) smear-negative TB suspects. Conclusions: Two cellular immune signatures could improve and accelerate diagnosis in the challenging group of patients who are IGRA-positive, AFB smear-negative, and have paucibacillary TB. Abstract : We evaluated the performance of cellular immune signatures for the diagnosis of active TB among IGRA-positive TB suspects in the UK. We identified a potential use for 2 tests in providing a high positive predictive value in paucibacillary cases.